(untitled) (Acta Scientiarum. Health Sciences, 2015)
The present study investigated the effects of short-chain fructooligosaccharides (scFOS) feeding on body weight, fat accumulation, glucose homeostasis and lipid profile in cafeteria (CAF) obese rats. Male Wistar rats were divided randomly into two groups: control group (CTL, n = 10), which received a chow diet and water and CAF (n = 20), which received the cafeteria diet, standard chow and soda. After 30 weeks of diet, 10 animals of CAF group received scFOS in the diet (50 g kg-1 of diet) over a period of 50 days, forming the CAF FOS group. Were evaluated the body weight, fat pad as well as, quantity of feces, glucose tolerance, insulin resistance (IR) and serum lipids levels. Animals submitted to the CAF diet displayed obesity, hyperglycemia, glucose intolerance, hyperinsulinemia and IR. The scFOS feeding not altered obesity, glucose intolerance, hyperinsulinemia and IR. CAF rats also presented hypertriglyceridemia and lower levels of HDL-cholesterol. The CAF FOS animals had reduced serum triglycerides (TG) and increased HDL-cholesterol. Thus, the use of scFOS in the diet can be considered as a hypolipidemic agent in the obese state.